Interannual variability of precipitation and moisture flux on Amazon using QTCM - Sousa, Aline Corrêa de; Cândido, Luiz Antônio; Andreoli, Rita Valéria (Revista Brasileira de Meteorologia, 2018)
The aim of this study was to evaluate the atmospheric response to the interannual variability patterns of Sea Surface Temperature in the areas of the Atlantic and Tropical Pacific, analyzing the seasonal cycle of Moisture Flux Divergence on the regions of the North and South Atlantic Tropical and Amazon. The Reanalysis data were used in the observational study, and the numerical study used the Quasi-equilibrium Tropical Circulation Model QTCM. The results show that QTCM has ability to represent the spatial distribution of precipitation maximum on the continent and its seasonal variations. QTCM plays the climatological patterns of precipitation and Moisture Flux Divergence associated with the occurrence of El Niño Southern Oscillation and Atlantic Meridional Mode, also suggesting that the seasonal average behavior of Moisture Flux Divergence in North Atlantic area, it has greater impact on the occurrence of El Niño, leading to reduced precipitation in the Amazon. North Atlantic area beyond the source of moisture is also an important regulator of Moisture Flux Divergence, whose temperature anomalies in this region provide impacts on the northern part of South America and Amazon. © 2018, Sociedade Brasileira de Meteorologia. All rights reserved.
Variabilidade Interanual da Precipitação e Fluxo de Umidade Sobre a Amazônia Usando o QTCM